Implementación experimental de un secador híbrido para reducción del tiempo en el secado de cacao mejorado. - Gavilema Orozco, Jhonny Washington (2021)
The technological proposal to build an experimental dryer for cocoa improved with the incentive of helping to reduce the drying time based on the consumption of thermal energy is proposed, taking into account that the proposal is constituted in solving a technical and economic problem, adhering to to the plan "a lifetime" in the mission of less poverty more development, mentions that the Ecuadorian citizen deserves to improve their socioeconomic situation, therefore it is estimated to execute from an ingenious perspective based on electromechanical knowledge [1]. Taking into account key points in the drying of improved cocoa as well as the advantages and disadvantages of natural and artificial drying. It is planned to study artificial drying together with a hybrid theme in what is energy consumption, it is known that artificial drying consumes petroleum-derived fuels and to be friendly to the environment, it will be chosen to add a second energy, but it is cleaner as is solar radiation, with this the help of fuel consumption will decrease a certain percentage being this suitable for the environment. With the improved cocoa hybrid experimental dryer, the optimization of drying time and quality is estimated, highlighting the speed of drying and quality of the cocoa so that the product is welcomed in the marketing stage.